Mail/parcel management system with SMS - Nurul Syuhada, Md Nasir (2013)
Mail Management System with SMS (MPMS) is developed to facilitate staffs and students of Residential College at Universiti Malaysia Pahang (UMP). This system can help and easily staff to manage the students’ parcel. In the existing system, process is conducted manually that consumes a lot of time and human effort. Therefore, the proposed system is to change the current process to computerized system and also provide Short Message Service (SMS). This system also can generate informative report about the parcel statistics. The methodology that has been applied in the project development is the prototype model. The advantage of prototype model is it can be an early act or representation of the final product and this method can reduce risk and limit expenses and costs. In the development of MPMS, PHP and MySQL has been used as programming tools. PHP is a scripting language widely used to write web applications while MySQL is an open source relational database management system. For the software, Adobe Dreamweaver CS4 has been used. As a result, web-based system and SMS are developed and this system helps increase the efficiency of mail management activity.